Gothenburg magnetic excursion in sediments of the Black Sea. - Demidenko, Evgeny L; Faustov, Stanislav S; Nikolaev, Sergey D (PANGAEA, 1998)
12 cores of Late Pleistocene - Holocene deposits were studied. They were collected by gravity cores on the continental slope and in the deep-water part of the Black Sea within the Adler-Tuapse polygon. In four of them in New Euxinian deposits at the base of a packet of hydrotroilite laminae paleomagnetic anomalies likely resulting from the Gothenburg magnetic excursion occur. Comparison with results of similar studies in the western Black Sea, where the Gothenburg magnetic excursion was previously found, let to validate stratigraphic synchronism of the hydrotroilite horizon in the eastern and western parts of the Black Sea and to confirm the authors' views about peculiarities of paleogeographical development of the Black Sea basin in the Late Pleistocene - Holocene.
Iron speciation and magnetic susceptibility in bottom sediments of the Black Sea, Core SMG91-903
Keywords: Archive of Ocean Data; ARCOD; Black Sea; DEPTH, sediment/rock; GC; Gravity corer; Iron; Iron, reactive; Iron monosulfide; Layer description; Magnetic susceptibility; Magnetic susceptibility detector; Pyrite, FeS2; SMG91-903; Wet chemistry